Diabetic cardiac autonomic neuropathy: a review of NLRP3 inflammasome complicity - Subramaniam, Shamala Devi; Mhd Zain, Nor Aini Lubis; Choy, Ker Woon; Omar, Noorkardiffa Syawalina; Abas, Razif (Universiti Putra Malaysia Press, 2024)
Debilitating and often misdiagnosed cardiac autonomic neuropathy affects people with diabetes. Damage to the biggest sympathetic trunk ganglion of autonomic nerve fibers that innervate the heart and blood vessels, the superior cervical ganglion (SCG), is the cause of aberrant heart rate and vascular dynamics in people with diabetic cardiac autonomic neuropathy (DCAN). Mediating host immunological responses to microbial infection and cellular damage, inflammasomes are a class of cytosolic protein complexes that include NLRP3. This review compiled the findings of experimental investigations on DCAN and discussed their connection to the NLRP3 inflammasome's involvement. SCG P2X7 receptor expression can be boosted by inflammation brought on by hyperglycemia, leading to nerve injury. Unfortunately, there is a lack of research on DCAN-related inflammation in animal models, especially in inflammasome. Currently, only IncRNAUC.360+ shRNA and Schisandrin B, prove to alleviate the pathogenesis. Therefore, more research into the causes and potential remedies for DCAN is necessary.